A Fast Frequency Sweep approach for performance-based optimization of earthquake-resistant irregular large-scale buildings. (15th June 2023) - de Salles, Humberto Brambila; Fadel Miguel, Leandro F.; Lenzi, Marcos Souza; Lopez, Rafael Holdorf; Beck, André Teófilo
Abstract: Performance-Based Design (PBD) optimization of buildings subjected to seismic excitations has increasingly been applied to regular small-scale structural systems to minimize initial or life-cycle costs. Nonetheless, a comprehensive bibliographic survey reveals that studies dealing with irregular buildings are scarce, although they can present higher seismic vulnerability than regular buildings. Specifically, the PBD optimization of irregular buildings represented by large-scale finite element (FE) models, and considering dozens of discrete design variables, cannot be found to the best of the authors' knowledge. Hence, this paper presents an original framework for the PBD optimization of irregular buildings subjected to seismic excitations, handling thousands of DOFs and dozens of discrete design variables. To relieve the computational burden, enabling the problem to be solved, a Model Order Reduction (MOR) strategy based on the Well-Conditioned Asymptotic Waveform Evaluation (WCAWE) approach is combined with a hybrid optimization algorithm, which integrates a local optimizer with a restart strategy. The former is employed to speed up the frequency-domain response, while the latter allows for tackling a non-convex and multimodal objective function with many discrete variables. The procedure is adaptatively devised to operate in a robust and fully black-box approach. The application case consists of a stiffness in-plane irregular H-shape building with 16, 452 active DOFs and 34 discrete design variables. The proposed scheme largely reduces the computational burden, leading to speed-up factors (SUF) up to 19 times compared to direct frequency-domain solutions. Highlights: PBD optimization of earthquake-resistant irregular large-scale buildings. Model Order Reduction (MOR) based on Fast Frequency Sweep (FFS). WCAWE approach performs the subspace projection of the FE matrices. Subspace order and the expansion points are automatically determined through AWA. Speed-up factors up to 19 times compared to complete frequency-domain solutions.